Intraoperative pedicle screw navigation does not significantly affect complication rates after spine surgery. (January 2018) - Wagner, Scott C.; Morrissey, Patrick B.; Kaye, Ian D.; Sebastian, Arjun; Butler, Joseph S.; Kepler, Christopher K.
Highlights: Computer-assisted navigation in spinal deformity surgery has questionable clinical benefits. Use of intraoperative navigation increased operative time by an average of 40 min. Navigation was not associated with reduction of any intra- or postoperative complications. Abstract: Various forms of intraoperative computer-assisted navigation technologies exist, and have consistently been shown to improve pedicle screw accuracy. However, the overall clinical effects of inaccurate pedicle screw placement have been debated. We examined the clinical effects of improved pedicle screw accuracy with computer navigation technology in reducing complication rates in patients undergoing multi-level spinal fusion. We retrospectively reviewed the ACS-NSQIP registry utilizing Current Procedural Terminology (CPT) codes 22843 + 22844 to identify patients undergoing spinal instrumentation of greater than 7 levels, as well as the CPT code 61783 to denote the use of intraoperative computer-assisted navigation. The data were then subdivided to into cohorts consisting of instrumentation cases with and without navigation. Demographic information, as well as intraoperative and postoperative complications, were compared between groups. A total of 3168 patients met our inclusion criteria. There were no statistically significant differences in preoperative population data. Surgical time was significantly longer in the navigation group (391.41 versus 350.3 min), but there were no significant improvements in complication rates with the use of navigation. We found that the mean operative time was significantly increased for patients undergoing spinal instrumentation with computer navigation. This increase in operative time was not associated with any increase in surgical or medical complications. However, in this large series, we were unable to show any clinical benefit to intraoperative navigation, and no reductions in short term complications or rates of return to surgery were observed.